Recent developments in topical thrombins - Kessler, Craig M.; Ortel, Thomas L. (Thrombosis and Haemostasis, 2009)
Managing blood loss is part of the surgeon’s responsibility during surgical procedures, and a variety of therapeutic strategies are available to help accomplish this. Topical haemostatic agents are among the agents used to control surgical bleeding and locally arrest blood flow. Bovine thrombin is a commonly used topical haemostatic agent; however, its use has been associated with potential risks, including well-documented cases of antibodymediated coagulopathy. This coagulopathy develops as a consequence of antibody formation directed against bovine thrombin, other bovine coagulation proteins, and their human orthologs. The fact that a coagulopathy can result in association with the use of bovine plasma-derived thrombin preparations prompted the FDA to require pharmaceutical companies to place a black-box warning in their prescribing information for products containing bovine plasma-derived thrombin. Recently, human plasma-derived thrombin and recombinant human thrombin have been approved by the FDA with the expectation that they will be less immunogenic than the bovine-derived product. In clinical studies, purified human plasma-derived thrombin and recombinant thrombin have demonstrated equivalent efficacy and safety, with improved immunogenicity profiles compared with bovinederived thrombin agents. Well-designed and adequately powered clinical trials should be conducted to indicate whether human thrombin products would improve the risk-benefit and costbenefit profiles for surgeries complicated by excessive bleeding.
Keywords: Bovine; coagulopathy; haemostasis; recombinant; thrombin